Implementasi Model Waterfall pada Pengembangan Sistem Informasi Monitoring Prestasi Mahasiswa - Devi Rahmawati; Annas Setiawan Prabowo; Riyadi Purwanto (Politeknik Negeri Cilacap, 2021)
Cilacap State Polytechnic (PNC) is a Polytechnic that has several scholarships in it. Bidikmisi is one of the scholarships available at PNC. Bidikmisi scholarship recipients are required to report their achievements every semester to the Biro Administrasi Akademik dan Kemahasiswaan (BAAK) which still often experiences problems, including student delays in collecting achievement reports, BAAK finds it difficult to monitor the progress of student achievement, especially in the non-academic field because all the data is in each student. This research focuses on monitoring related to student achievement. Making this system using the waterfall method because it is systematic. The results of the questionnaire show that this system can assist in the process of managing and monitoring student achievement with a percentage of around 60% stating it is good and can help students to notify the results of their achievements and can be accessed at any time without having to wait for information or visit the BAAK room with a high percentage. obtained from the results of the questionnaire about 70% stated good